A simple and environmentally friendly reflectometric method for the rapid quantitative analysis of captopril in pharmaceutical formulations - Ribeiro, Paulo Roberto S.; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (My University, 2011)
This paper describes a simple, environmentally friendly and rapid quantitative spot test procedure for the determination of captopril (CPT) in bulk drug and in pharmaceutical formulations by using diffuse reflectance spectroscopy. The proposed method is based on the reflectance measurements of the orange compound (λ max 490 nm) produced by the spot test reaction between CPT and p-chloranil (CL). Under optimal conditions, calibration curves were obtained for CPT by plotting the optical density of the reflectance signal (A R) vs. the log of the mol L -1 concentration, from 6.91×10 -3 to 1.17×10 -1, with a good coefficient of determination (R 2 = 0.9992). The common excipients used as additives in pharmaceuticals do not interfere in the proposed method. The method was applied to determine CPT in commercial pharmaceutical formulations. The results obtained by the proposed method are compared favorably with those obtained by an official procedure at 95% confidence level. The method validation results showed that the sensitivity and selectivity of the methods were adequated for drug monitoring in industrial quality control laboratories. © 2011 Moment Publication.
Keywords: Captopril; Charge transfer complex; Diffuse reflectance; Pharmaceutical formulations; captopril; chloranil; excipient; chemical reaction; controlled study; diffuse reflectance spectroscopy; green chemistry; optical density; quality control; quantitative analysis; sensitivity analysis